Exploring Emotional Intelligence: A Correlational Study of Follower Attributes - Prilipko, Evgenia V.; Beauford, Judith E.; Antelo, Absael (Journal of Management Policy and Practice, 2019)
Emotional intelligence is an important characteristic of good leaders and followers. In this work, the relationship between emotional intelligence and the other follower attributes is examined. For the first time, a strong correlation between emotional intelligence and flexibility, tolerance of differing views, and facility for supporting others is demonstrated.